Palm Trees, Trinidad, B.W.I. - (:unkn) unknown (Stephens and Scott Ltd., The Stores, Trinidad, 2010)
The postcard shows six stately palms in the Queen's Park Savannah, Port of Spain, Trinidad.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mountains--Trinidad and Tobago; Savannas--Trinidad and Tobago; Palms--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; [1900]; Queen's Park Savannah (Port of Spain)